Optimization of Pyrolysis for MgO Recycling in Magnesia-Based Flue Gas Desulfurization - Kang, Wanzhong; Zhou, Yanbo; Shen, Zhigang; Tang, Xuanyi; Lu, Jun (Asian Journal of Chemistry, 2012)
The magnesia (MgO)-based flue gas desulfurization process can effectively remove sulfur dioxide and the absorbent-MgO can be recycled via the pyrolysis of the major flue gas desulfurization byproduct MgSO3. In the current study, the pyrolysis conditions of the flue gas desulfurization byproducts was optimized to achieve efficient MgO recycling in the laboratory. The optimal pyrolysis conditions were 550 ºC and 10 K/min heating rate. The dried MgSO3 was found to have higher decomposition efficiency than the sample with moisture. The decomposition efficiency of MgSO3 reached 90 %, whereas the MgO content in the pyrolyzed product reached 70 % and had ideal reactivity. The actual byproducts from the power plant were also pyrolyzed under the optimal conditions and compared with the MgSO3 samples produced in laboratory. Given the existence of impurities, the pyrolysis effect of the actual byproducts was slightly inferior to the laboratory-produced MgSO3. Therefore, the impurity content of the byproducts must be decreased to efficiently recycle MgO.